IMPROVING THE QUALITY OF MATHEMATICS EDUCATION THROUGH INNOVATIVE APPROACHES: A LITERATURE REVIEW - Adi Asmara; Winda Ramadianti, Rahmat Jumri, Ristontowi, Masri (International Journal of Teaching and Learning, 2024)
This literature review explores the potential avenues for enhancing the quality of mathematics education through innovative approaches. The analysis encompasses conventional and emerging methodologies, focusing on problem- based learning, gamification, and inquiry-based strategies. The study evaluates the strengths and limitations of these approaches, drawing insights from empirical studies to underscore their impact on student engagement and achievement. Additionally, the review addresses challenges faced at the student and teacher levels, proposing strategies such as comprehensive teacher training and technological support. The implications for mathematics education are discussed, emphasizing the need for a balanced integration of conventional and innovative methods. Recommendations for future research highlight potential areas for further exploration, including the long-term impact of innovative approaches on student learning outcomes. This comprehensive literature review is a valuable resource for educators, policymakers, and researchers seeking to optimize the quality of mathematics education.